Prevalence of cesarean section on demand in Assiut Governorate, Egypt - Zakherah, Mahmoud S.; Farghaly, Tarek A.; Ahmed, Elham S.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The current study aims to evaluate the prevalence of CS on demand in Women's health hospital, Assiut University and Abnob Central Hospital in Assiut Governorate, Egypt. Methods: A cross sectional study conducted in Assiut Women Health Hospital and Abnob central hospital from January 2017 to December 2017. The total number of cesarean section done was 180 cases and the number of CS on demand was 64 (35.6%). The demographic data were collected by one of the study investigators. Women were asked about the causes of requesting CS before surgery. Results: The study group was 64 women with age ranging from 18-40 years old, 40 primipara and 24 multipara. Of those 24 women, 21 of them previously delivered vaginally and only 3 women delivered by emergency CS. Twenty- six women had a history of previous abortion. Fear of pain was the main cause for CS on demand in the whole study participants (57.8%). In primipara, the main cause for requesting CS is fear of pain in 62.5% of participants followed by fear on the baby in 45 % of women. On the other hand, in multipara, the main cause for CS on demand was bad history of previous experience (60%) followed by fear of pain in 50% of cases. There was statistical significant difference between both groups in only two causes; fear of pelvic floor injuries (50% in multipara vs. 20% in primipara, p=0.02) and bad history of previous experience (60% in multipara vs. 0% in primipara, p=0.001). Other causes were not statistically different. Conclusions: The incidence of cesarean sections performed on request without medical indications is rising. The reasons for this are not only for perceived medical benefit, but also due to social, cultural, and psychological factors.